Anti-Helicobacter pylori potential of Agrimonia eupatoria L. and Fragaria vesca. (May 2018) - Cardoso, Olga; Donato, Maria Manuel; Luxo, Cristina; Almeida, Nuno; Liberal, Joana; Figueirinha, Artur; Batista, Maria Teresa
Abstract: Helicobacter pylori ( H. pylori ) plays a causal role in chronic gastritis, peptic ulcer and gastric cancer. Antibiotic resistance and side effects of therapy have led to research for new candidates. Susceptibility and virulence factors were studied in H. pylori 12 clinical isolates. Agrimonia eupatoria L. (Ag), Fragaria vesca (Fv) extracts and a Fv ellagitannin-enriched fraction (Fve) activity were tested against these isolates. Ag, Fv extracts and Fve presented activity against H. pylori multi-resistant and virulent. Fve demonstrated the best activity (5 mg/mL inhibited 67% of isolates), follow by Fv (12.5 mg/mL inhibited 58%) and by Ag (25 mg/mL inhibited 40%). This is the first report of Fv extract and Fve fraction activity on H. pylori isolates. These activity and that of Ag were independently of the different patterns of virulence and susceptibility, suggesting potential of these plants as new natural drugs or as bioactive agents in association with antibiotic therapy.